PENGUJI MANIPULASI LABA REAL PADA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA) - Yateno Yateno; Gustin Padwa Sari (Universitas Muhammadiyah Metro, 2016)
This study aims to examine empirically the effect of real earnings manipulation to CSR disclosure. A proxy for real earnings manipulation using models Roychowdhury (2006). CSR disclosure is measured using Corporate Social Disclosure Index (CSDI) based item reporting standard Global Reporting Initiative (GRI) are disclosed in the company's annual report. The study sample consisted of 261 manufacturing companies in 2012-2014. The results showed real earnings manipulation significant positive effect on CSR disclosure.Keywwords: Earnings Manipulation, Corporate Social Responsibility, Manufacturing Companies.